Neural Information Processing 29th International Conference, ICONIP 2022, Virtual Event, November 22-26, 2022, Proceedings, Part I - Tanveer, Mohammad; Agarwal, Sonali; Ozawa, Seiichi; Ekbal, Asif.; Jatowt, Adam. (Cham : Springer International Publishing : Imprint: Springer, 2023)
The three-volume set LNCS 13623, 13624, and 13625 constitutes the refereed proceedings of the 29th International Conference on Neural Information Processing, ICONIP 2022, held as a virtual event, November 22-26, 2022. The 146 papers presented in the proceedings set were carefully reviewed and selected from 810 submissions. They were organized in topical sections as follows: Theory and Algorithms; Cognitive Neurosciences; Human Centered Computing; and Applications. The ICONIP conference aims to provide a leading international forum for researchers, scientists, and industry professionals who are working in neuroscience, neural networks, deep learning, and related fields to share their new ideas, progress, and achievements.
Theory and Algorithms -- Solving Partial Differential Equations using Point-based Neural Networks -- Patch Mix Augmentation with Dual Encoders for Meta-Learning -- Tacit Commitments Emergence in Multi-agent Reinforcement Learning -- Saccade Direction Information Channel -- Shared-Attribute Multi-Graph Clustering with Global Self-Attention -- Mutual Diverse-Label Adversarial Training -- Multi-Agent Hyper-Attention Policy Optimization -- Filter Pruning via Similarity Clustering for Deep Convolutional Neural Networks -- FPD: Feature Pyramid Knowledge Distillation -- An effective ensemble model related to incremental learning in neural machine translation -- Local-Global Semantic Fusion Single-shot Classification Method -- Self-Reinforcing Feedback Domain Adaptation Channel -- General Algorithm for Learning from Grouped Uncoupled Data and Pairwise Comparison Data -- Additional Learning for Joint Probability Distribution Matching in BiGAN -- Multi-View Self-Attention for Regression Domain Adaptation with Feature Selection -- EigenGRF: Layer-Wise Eigen-Learning for Controllable Generative Radiance Fields -- Partial Label learning with Gradually Induced Error-Correction Output Codes -- HMC-PSO: A Hamiltonian Monte Carlo and Particle Swarm Optimization-based optimizer -- Heterogeneous Graph Representation for Knowledge Tracing -- Intuitionistic fuzzy universum support vector machine -- Support vector machine based models with sparse auto-encoder based features for classification problem -- Selectively increasing the diversity of GAN-generated samples -- Cooperation and Competition: Flocking with Evolutionary Multi-Agent Reinforcement Learning -- Differentiable Causal Discovery Under Heteroscedastic Noise -- IDPL: Intra-subdomain adaptation adversarial learning segmentation method based on Dynamic Pseudo Labels -- Adaptive Scaling for U-Net in Time Series Classification -- Permutation Elementary Cellular Automata: Analysis and Application of Simple Examples -- SSPR: A Skyline-Based Semantic Place Retrieval Method -- Double Regularization-based RVFL and edRVFL Networks for Sparse-Dataset Classification -- Adaptive Tabu Dropout for Regularization of Deep Neural Networks -- Class-Incremental Learning with Multiscale Distillation for Weakly Supervised Temporal Action Localization -- Nearest Neighbor Classifier with Margin Penalty for Active Learning -- Factual Error Correction in Summarization with Retriever-Reader Pipeline -- Context-adapted Multi-policy Ensemble Method for Generalization in Reinforcement Learning -- Self-attention based multi-scale graph convolutional networks -- Synesthesia Transformer with Contrastive Multimodal Learning -- Context-based Point Generation Network for Point Cloud Completion -- Temporal Neighborhood Change Centrality for Important Node Identification in Temporal Networks -- DOM2R-Graph: A Web Attribute Extraction Architecture with Relation-aware Heterogeneous Graph Transformer -- Sparse Linear Capsules for Matrix Factorization-based Collaborative Filtering -- PromptFusion: a Low-cost Prompt-based Task Composition for Multi-task Learning -- A fast and efficient algorithm for filtering the training dataset -- Entropy-minimization Mean Teacher for Source-Free Domain Adaptive Object Detection -- IA-CL: A Deep Bidirectional Competitive Learning Method for Traveling Salesman Problem -- Boosting Graph Convolutional Networks With Semi-Supervised Training -- Auxiliary Network: Scalable and agile online learning for dynamic system with inconsistently available inputs -- VAAC: V-value Attention Actor-Critic for Cooperative Multi-agent Reinforcement Learning -- An Analytical Estimation of Spiking Neural Networks Energy Efficiency -- Correlation Based Semantic Transfer with Application to Domain Adaptation -- Minimum Variance Embedded Intuitionistic Fuzzy Weighted Random Vector Functional Link Network -- Neural Network Compression by Joint Sparsity Promotion and Redundancy Reduction.
Keywords: Pattern recognition systems; Data mining; Machine learning; Social sciences -- Data processing; Automated Pattern Recognition; Data Mining and Knowledge Discovery; Machine Learning; Computer Application in Social and Behavioral Sciences